Development of a smart factory prototype in context of industry 4.0 - Mohammad, Ubaidullah (2020)
The disruption caused by digitalization and the Internet, the increase in labour costs and the demand for a better work-life balance have led to the emergence of the fourth industrial revolution or also called Industry 4.0. In this work, a smart factory prototype was developed to showcase the application of digitalization, data exchange, Internet of things, system integration and usage of ICT in a manufacturing system, in order to automatically produce a customized product. The smart factory concept was specified by a system model showing the system’s elements and its dependencies. A prototype was constructed by retrofitting a modular trainer with Industry 4.0 elements while using currently available components such as RFID, PLC and network components, which was connected to a local area network with an Internet connection. A SCADA software was used as the backbone of the system to interface various devices for monitoring, control, and data exchange to a database. It was also used to build a user interface for local and remote access through the Internet. Evaluations based on the VDMA Industry 4.0 Toolbox were conducted in terms of functionality and Industry 4.0 application level. The prototype managed to increase its Industry 4.0 application level from 0.3 to 2.3 from a maximum level of 4.0 according to the VDMA toolbox. In conclusion, the smart factory prototype that was developed by retrofitting an existing system can be used to showcase the concept of Industry 4.0 to improve understanding on Industry 4.0.